Flouting Maxim of Quality in Situational Comedy ‘Lapor Pak’ - Rini Afrilesa J (Fakultas Sastra Universitas Ekasakti, 2022)
This research conducted on flouting quality maxim uttered by the actors and actress in the Lapor Pak Comedy. The problems of the research are: (1) What floutings forms of quality maxim are gone through by the actors and actress in Lapor Pak Comedy? (2) What are the reasons of the actors/actress flouted the maxims of quality? The purposes of this research are: (1) To identify forms of flouting quality maxims sustained by actors/actress in Lapor Pak Comedy (2) To describe the contextual meanings which are used by the actors/actress who flouted the maxims of quality. Descriptive qualitative method had been used in this research. This research used theory of Grice (1975). The results of this study are as follows that there 13 data have found and flouting quality maxim divided into four forms. They are Flouting maxim quality in Mocking dialogue, Flouting maxim quality in Wordplay dialogue, Flouting maxim quality in Babble dialogue, and Flouting maxim quality in Accuse Without Evidence dialogue. The reason that was flouting quality maxim often used in this comedy is giving humor.